2018
DOI: 10.1681/asn.2018010096
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and Pregabalin Use and Association with Adverse Outcomes among Hemodialysis Patients

Abstract: Gabapentin and pregabalin are used to manage neuropathic pain, pruritus, and restless legs syndrome in patients on hemodialysis. These patients may be especially predisposed to complications related to these agents, which are renally cleared, but data regarding the risk thereof are lacking. From the US Renal Data System, we identified 140,899 Medicare-covered adults receiving hemodialysis with Part D coverage in 2011. Using Cox regression models in which we adjusted for demographics, comorbidities, duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 52 publications
3
72
0
3
Order By: Relevance
“…A total of 17 journal articles were identified and assessed for eligibility. Nine were excluded because of the following reasons: one was a pilot study, two were reviews, two were retrospective studies, one was a protocol, one was a correspondence letter, and three were nonrandomized clinical trials (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 17 journal articles were identified and assessed for eligibility. Nine were excluded because of the following reasons: one was a pilot study, two were reviews, two were retrospective studies, one was a protocol, one was a correspondence letter, and three were nonrandomized clinical trials (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…one was a pilot study, 4 two were reviews, 8,11 two were retrospective studies, 12,13 one was a protocol, 14 one was a correspondence letter, 15 and three were nonrandomized clinical trials [16][17][18] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…These concerns have been highlighted in clinical guidelines, which have advocated conservative dosing [39]. This is also an issue given studies which document prescription at higher doses than recommended [23]. Pregabalin, an anticonvulsant indicated to treat neuropathic pain, has also been associated with neurotoxicity in patients with chronic kidney disease [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns over gabapentinoid abuse and risks of toxicity among ESRD patients have been raised previously [21,22]. Ishida et al [23] reported prescription of gabapentinoids was common in ESRD patients and associated with altered mental status and falls. We showed prescription of gabapentin to dialysis patients with a diagnosis of seizures or epilepsy was associated with increased mortality [24].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, pregabalin in doses of up to 100 and ˃ 100 mg/d increased the likelihood of altered mental status issues by 51% and 46% of patients, respectively. Gabapentin was more commonly prescribed (19%) than was pregabalin (4%) …”
mentioning
confidence: 99%